Analysis of Finite Source Traffic Model of Wireless LAN: A Case Study - Indar Surahmat; Satrya Try Manggala (Journal of Electrical Technology UMY, 2017)
Investigating characteristics of users and their pattern to access networks are parts of important points in traffic engineering. In this paper, those problems, specifically in wireless LAN, were observed and some related theories were explored. The observation was done in UMY, a campus located in Yogyakarta, Indonesia. In this term, we examined the traffic in an Wireless Action Point. Resuming the content of this paper, we found that the traffic had unique characteristics. For instance, during the day of measurement, the peaks of traffic were in the morning and in the afternoon. Average connected clients in all action points in UMY was between 2500 and 3000 users. When we selected an AP, the characteristic of the AP was examined, the number data size are 62.99 MB and 129.22 MB for mean and standard deviation respectively. We found that hourly trend of the usage of APs resembled self-similar model.